2009
DOI: 10.3748/wjg.15.2214
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of confocal endomicroscopy in the diagnosis of pediatric gastrointestinal disorders

Abstract: AIM:To evaluate the feasibility and utility of confocal laser endomicroscopy (CLE) in the description of normal gastrointestinal (GI) mucosa and in the diagnosis of GI disorders in children, in comparison to histology. METHODS:Forty-four patients (19 female) median age 10.9 years (range 0.7-16.6 years) with suspected or known GI pathology underwent esophago-gastroduodenoscopy (OGD) (n = 36) and/or ileocolonoscopy (IC) (n = 31) with CLE using sodium fluorescein and acriflavine as contrast agents. Histological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
0
23
0
2
Order By: Relevance
“…2,19 This benefit was validated in its application to gastrointestinal and gynecological surgery. 5,[15][16][17][18] We have investigated the feasibility of CLE in a murine malignant glioma model to distinguish normal brain, microvasculature, and tumor margins. 4,8,9,14 Furthermore, we have demonstrated its potential application as an intraoperative tool in human brain tumor surgery.…”
mentioning
confidence: 99%
“…2,19 This benefit was validated in its application to gastrointestinal and gynecological surgery. 5,[15][16][17][18] We have investigated the feasibility of CLE in a murine malignant glioma model to distinguish normal brain, microvasculature, and tumor margins. 4,8,9,14 Furthermore, we have demonstrated its potential application as an intraoperative tool in human brain tumor surgery.…”
mentioning
confidence: 99%
“…3d,e) when using intravenous fluorescein as a contrast agent. Other studies have shown that endomicroscopy can diagnose coeliac disease [55][56][57][58] based on recognition of features relevant to EED, such as villous atrophy, crypt hyperplasia and lymphocyte infiltration. In particular, Venkatesh et al 58 reported successful diagnosis of coeliac disease (100% sensitivity, 80% specificity) in children as young as 1.8 years of age.…”
Section: Microbiota Changesmentioning
confidence: 99%
“…Other studies have shown that endomicroscopy can diagnose coeliac disease [55][56][57][58] based on recognition of features relevant to EED, such as villous atrophy, crypt hyperplasia and lymphocyte infiltration. In particular, Venkatesh et al 58 reported successful diagnosis of coeliac disease (100% sensitivity, 80% specificity) in children as young as 1.8 years of age. Semi-automated methods for the detection and segmentation of villi 56 and for the measurement of goblet cell density 57 have also been presented.…”
Section: Microbiota Changesmentioning
confidence: 99%
“…However, the penetration depth of LSM is limited due to two factors: background due to out-of-focus scattering and signal-to-noise ratio (Schmitt et al, 1997). Recently, a confocal microscope has been miniaturized and integrated into a conventional flexible endoscope (Venkatesh et al, 2009). The diameter of the distal tip of the endoscope is 12.8 mm including the integrated miniaturized confocal microscope with a diameter of 5 mm (Venkatesh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a confocal microscope has been miniaturized and integrated into a conventional flexible endoscope (Venkatesh et al, 2009). The diameter of the distal tip of the endoscope is 12.8 mm including the integrated miniaturized confocal microscope with a diameter of 5 mm (Venkatesh et al, 2009). The use of endoscopes with this large diameter has so far been limited to the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%